summaryrefslogtreecommitdiff
path: root/libraries
diff options
context:
space:
mode:
authorHerbert Valerio Riedel <hvr@gnu.org>2015-10-18 09:20:30 +0200
committerHerbert Valerio Riedel <hvr@gnu.org>2015-10-18 09:39:26 +0200
commitc6781a5064049e0a7c17c1f2239567a3c44955af (patch)
tree273862930c0878da546c7124736d0fd020ab2f8b /libraries
parent75c7cda2a2931bccbb7af5a76278729fccbe4228 (diff)
downloadhaskell-c6781a5064049e0a7c17c1f2239567a3c44955af.tar.gz
template-haskell: MRP-refactor Applicative/Monad instances
As `template-haskell` is compiled by stage1+ GHC only, we can drop the explicit `return` definition rightaway.
Diffstat (limited to 'libraries')
-rw-r--r--libraries/template-haskell/Language/Haskell/TH/PprLib.hs3
-rw-r--r--libraries/template-haskell/Language/Haskell/TH/Syntax.hs4
2 files changed, 3 insertions, 4 deletions
diff --git a/libraries/template-haskell/Language/Haskell/TH/PprLib.hs b/libraries/template-haskell/Language/Haskell/TH/PprLib.hs
index 8019e48205..e398094fef 100644
--- a/libraries/template-haskell/Language/Haskell/TH/PprLib.hs
+++ b/libraries/template-haskell/Language/Haskell/TH/PprLib.hs
@@ -154,11 +154,10 @@ instance Functor PprM where
fmap = liftM
instance Applicative PprM where
- pure = return
+ pure x = PprM $ \s -> (x, s)
(<*>) = ap
instance Monad PprM where
- return x = PprM $ \s -> (x, s)
m >>= k = PprM $ \s -> let (x, s') = runPprM m s
in runPprM (k x) s'
diff --git a/libraries/template-haskell/Language/Haskell/TH/Syntax.hs b/libraries/template-haskell/Language/Haskell/TH/Syntax.hs
index 8d56a98dc8..607e6da92c 100644
--- a/libraries/template-haskell/Language/Haskell/TH/Syntax.hs
+++ b/libraries/template-haskell/Language/Haskell/TH/Syntax.hs
@@ -159,9 +159,8 @@ runQ :: Quasi m => Q a -> m a
runQ (Q m) = m
instance Monad Q where
- return x = Q (return x)
Q m >>= k = Q (m >>= \x -> unQ (k x))
- Q m >> Q n = Q (m >> n)
+ (>>) = (*>)
fail s = report True s >> Q (fail "Q monad failure")
instance Functor Q where
@@ -170,6 +169,7 @@ instance Functor Q where
instance Applicative Q where
pure x = Q (pure x)
Q f <*> Q x = Q (f <*> x)
+ Q m *> Q n = Q (m *> n)
-----------------------------------------------------
--